Urgensi Mediasi dalam Penyelesaian Sengketa Perceraian di Pengadilan Agama Purwakarta: Upaya Meningkatkan Efektivitas Penyelesaian Perkara dan Meminimalkan Dampak Sosial - Sofia Gussevi; Aden Rosadi; Usep Saepullah; Tajul Muttaqin; Jihan Fatiha Alman (Muttaqien Publishing, Lembaga Penelitian dan Pengabdian kepada Mayarakat (P3M) STAI DR. KH.EZ. Muttaqien Purwakarta, 2025)
Divorce resolution through litigation in the Religious Courts often has long-lasting social and psychological effects, especially for children and other family members. To mitigate these negative impacts, the Indonesian legal system requires mediation in all civil cases, including divorce, by Supreme Court Regulation (PERMA) No. 1 of 2016. This study explores the importance of mediation in resolving divorce disputes in the Purwakarta Religious Court, identifies existing challenges, and formulates strategies to improve mediation's effectiveness. The method used is normative juridical with a qualitative approach, supported by secondary data such as regulations, court decisions, and scientific literature. The results show that mediation plays an important role in achieving amicable settlements and reducing the caseload in court. However, the effectiveness of mediation remains low due to a lack of public understanding, a small number of certified mediators, and limited supporting facilities. Therefore, strategic steps are needed, such as increasing the capacity of mediators and providing adequate facilities, so mediation can be an effective solution in resolving divorce disputes.